The Effect of Leadership Style and Work Discipline on Employee Performance at PT. Dalani Terang Persada - Posman WH Hasibuan; Swasta Bangun (Journal of Research in Business, Economics, and Education, 2021)
This study was conducted to determine how far the influence of leadership style and work discipline on employee performance at PT. Dalani Terang Persada. The research conducted is by distributing questionnaires, while the research method used is by using quantitative methods. In conducting this research, the writer uses correlation coefficient analysis, multiple linear regression using t test and F test. From the results of multiple linear regression analysis, the authors obtain the equation Y = 7.831 + 0.158 X1 + 0.531 X2, which means any increase or decrease in the variable leadership style (X1) is 1 point, the employee performance variable (Y) will increase or decrease by 0.158. In the work discipline variable (X2), for every 1-point increase or decrease, the employee's performance (Y) will increase or decrease by 0.631. From the relationship analysis, the correlation coefficient is shown by the simultaneous coefficient value of 0.735, which means that the two independent variables have a strong relationship with the dependent variable. and work discipline. From the results of the F test obtained a value of 15.83 where the value is greater than F table 3.35 thus Ho is rejected and Ha is accepted, meaning that simultaneously leadership style and work discipline can affect employee performance. In the t-test, it is known that the t-count for leadership style (X1) is 2.320 while the t-count column for discipline (X2) is 3.793 using the t-normal distribution table and using the error rate (α) = 5% and degrees of freedom (degree of freedom) or (df) n – 3 = 30 – 3 = 27, then the value of the distribution of table t is 2.051. Because the t count of leadership style is greater than t table or 2.320 > 2.051, then H0 is rejected and Ha is accepted, and because the t-count value of work discipline is greater than t table or 3.793 > 2.051, then Ho is rejected and Ha is accepted. Therefore, the Leadership Style and Work Discipline can partially affect the performance of employees at PT. Dalani Bright Persada.